Review of design works for the conversion of sugarcane to first and second-generation ethanol and electricity. (August 2018) - Bechara, Rami; Gomez, Adrien; Saint-Antonin, Valérie; Schweitzer, Jean-Marc; Maréchal, François; Ensinas, Adriano
Abstract: The conversion of sugarcane, the world's largest crop, to energy vectors, namely first and second-generation ethanol and electricity, is an ongoing scientific endeavor. This conversion makes use of complex processes with numerous unit operations and process blocks addressed in literature. Such processes have also been the subject of detailed thermo-economic and techno-economic evaluations as well as the application of systematic methodologies involving simulation, heat integration, optimization and selection. Key works related to this field are discussed in this review along with their hypotheses and results. The main future technologies are also presented. This review is realized to provide the scientific community with accessible references, information and ideas that will ultimately help researchers build consolidated and optimal designs for this process.